Efeito do tratamento térmico em cerâmica feldspáticas silanizada na adesão do cimento resinoso - Miranda, Geraldo Marques [UNESP] (2014)
The conventional surface treatment performed on feldspathic ceramic is the fluoridric acid etching and silane application. But in several studies the etching has been questioned for its chemical toxicity. Thus this study aimed to evaluate the effect of heat treatment on silanized feldspathic ceramic bond strength to resin cement. Through an in vitro study 24 feldspathic ceramic sintered blocks were sectioned; 5 x 10 x 4 mm of dimensions. These blocks were randomly divided into three experimental groups: G1 ( HF + silane ) ; G2 ( + Silane heating 77 °C); (G3 + Silane + HF + heating 77 °C). The ceramic blocks were cemented with resin blocks composed of resinous cement ( Variolink , IvoclairVivadent ) , the set was later cemented identical blocks of composite resin ( Z - 100 , 3M - ESPE ) , after cementation were subjected to cycling mechanical (10,000 cycles 100 N). After cycling were sectioned into sticks of 1mm2 and submitted to microtensile test with speed of 1 mm / min. Representative samples were analyzed with a stereomicroscope at 20 x and scanning electron microscope with magnitudes of 100 x, 300 x and 500 x. The results were statistically analyzed by ANOVA one factor and by Tukey test (α = 0.05). Statistical analysis showed (p - value = 0.33) statistical similarity between all groups (G1 22.63 mPa, mPa 23.31 G2, G3 26.32 mPa). The failure analysis showed predominance of adhesive failures for all groups. It can be concluded that heating the silane is effective for this interface it is possible to eliminate the etching with HF (Flouridric acid)